Horizontal Mergers with Capital Adjustments: Workers' Cooperatives and the Merger Paradox - Flavio Delbono; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We study the incentives towards horizontal merger among firms when the amount of capital is the strategic variable. The type of firms we focus on is workers' cooperatives, but our conclusions apply also to employment-constrained profit maximisers. Within a simple oligopoly model, we prove that the horizontal merger, for any merger size, is: (i) privately efficient for insiders as well as for outsiders; (ii) socially efficient if market size is large enough, including the case of merger to monopoly.
Keywords: D43; L13; L21; L41; 330